2008
DOI: 10.1002/ijc.23637
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of metastasis‐associated gene expression in primary cultures from clinical specimens of clear‐cell renal‐cell carcinoma

Abstract: Metastatic clear-cell renal-cell carcinoma (ccRCC) has a poor prognosis and unpredictable course, and there are no molecular markers that reliably predict ccRCC metastasis. In this study, ccRCC specimens from 84 patients were directly cultured in vitro. Primary cultures from 38 of 94 specimens contained more than 90% tumor cells at the fourth passage. After identification by immunostaining, the primary cultures of metastatic and nonmetastatic ccRCC specimens from the age-and gender-matched patients were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 54 publications
(135 reference statements)
5
53
0
Order By: Relevance
“…The rate of success in establishing primary cultures was not correlated with clinical-pathological characteristics of neoplastic patients. The growth rate and survival data of our cultures were in agreement with those described by others 33,34 and indicated that RCC cultures have a longer doubling time attributable to differences in cell loss, and probably in growth fraction and in length of cell cycle time as we can hypothesize from literature data. [35][36][37] FACS and immunofluorescence demonstrated that our cortex cultures were essentially composed of epithelial tubular cells of proximal and distal origin, whereas RCC cultures were composed of neoplastic cells derived from proximal tubule cells.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of success in establishing primary cultures was not correlated with clinical-pathological characteristics of neoplastic patients. The growth rate and survival data of our cultures were in agreement with those described by others 33,34 and indicated that RCC cultures have a longer doubling time attributable to differences in cell loss, and probably in growth fraction and in length of cell cycle time as we can hypothesize from literature data. [35][36][37] FACS and immunofluorescence demonstrated that our cortex cultures were essentially composed of epithelial tubular cells of proximal and distal origin, whereas RCC cultures were composed of neoplastic cells derived from proximal tubule cells.…”
Section: Discussionsupporting
confidence: 91%
“…These reports, together with our previously study,7 suggested that GSTM3 might function as a suppressor in tumour progression. Elevated ROS activity also played an important role in cancer cell survival and development 14.…”
Section: Discussionsupporting
confidence: 78%
“…The fresh surgical specimens of ccRCC from 17 patients were harvested and immediately immersed in ice‐cold PBS containing 1% penicillin/streptomycin and 0.5% glutamine (Beyotime, Shanghai, China). Primary cell culture was performed within 60 min after surgery as previously described 7. As a variation of phenotype might occur at higher passages, we chose the ccRCC cultures at the fourth passage for functional experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to tissue availability, genome-wide interrogation of biomarkers associated with metastatic progression and cancerspecific death has primarily been based on observations made in the primary tumor [6][7][8] and not in the more lethal, and more therapeutically relevant metastatic lesion. And, genome-wide studies that have preliminarily interrogated metastatic specimens have done so using small sample sizes [9,10]. Thus, the molecular mechanisms that lead to RCC metastases remain largely unknown and require further study.…”
Section: Introductionmentioning
confidence: 99%